RNAi of Sterol Δ24-Isomerase Implicated Its Involvement in Physalin Biosynthesis in Physalis angulata L. - Yang, Jiao; Tian, Jingyi; Yang, Yuhui; Zhu, Yaru; Li, Changfu; Zhang, Yansheng (Frontiers in Plant Science, 2022)
Physalis angulata is a renowned traditional Chinese medicine for treatment of various conditions. Physalin is the major type of bioactive constituents conferring medicinal properties of P. angulata. Despite the medicinal importance, the pathways leading to physalin are largely unknown. In this study, we employed a transcriptomic approach to identify a Pa24ISO gene from P. angulata. Through heterologous expression in yeast, Pa24ISO was revealed to catalyze an isomerization reaction in converting 24-methylenecholesterol to 24-methyldesmosterol. Real-time PCR analysis showed that the abundance of Pa24ISO transcripts correlated with the accumulation pattern of physalin B in different tissues of P. angulata. A direct role of Pa24ISO in channeling of 24-methylenecholesterol for physalin B biosynthesis was illustrated by suppressing the gene in P. angulata via the VIGS approach. Down-regulation of Pa24ISO led to reduced levels of 24-methyldesmosterol and physalin B, accompanied with an increase of campesterol content in P. angulata. The results supported that 24ISO is involved in physalin biosynthesis in plants.